2022
DOI: 10.3389/fped.2022.1007730
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of central precocious puberty more than doubled during COVID-19 pandemic: Single-center retrospective review in the United States

Abstract: Background and aim of the studyThe frequency of new visits for precocious puberty increased during the Covid-19 pandemic in the pediatric endocrinology clinic at Rady Children's Hospital in San Diego, CA, US. A few recent studies have shown an increase in the frequency of Central Precocious Puberty (CPP) in other centers during this pandemic. This study evaluated the change in incidence of new CPP cases requiring treatment with GnRH agonist (GnRHa) at Rady Children's Hospital during the Covid-19 pandemic and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…reported than double incidence of CPP in Turkish girls during the pandemic compared to the previous three-years; no significant increase in BMI SDS compared to the pre-pandemic period was reported ( 112 ), suggesting that factors other than increased BMI played a role in the development of CPP. Similar data have been reported in Korean ( 103 ), Turkish ( 115 , 117 ), Indian ( 116 ), Chinese ( 113 , 121 ), Spanish ( 114 ), Brazilian ( 120 ), Lebanese ( 125 ) and American girls ( 126 ) ( Table 1 ).…”
Section: Precocious Puberty During the Covid-19 Pandemic: Current Dat...supporting
confidence: 86%
See 2 more Smart Citations
“…reported than double incidence of CPP in Turkish girls during the pandemic compared to the previous three-years; no significant increase in BMI SDS compared to the pre-pandemic period was reported ( 112 ), suggesting that factors other than increased BMI played a role in the development of CPP. Similar data have been reported in Korean ( 103 ), Turkish ( 115 , 117 ), Indian ( 116 ), Chinese ( 113 , 121 ), Spanish ( 114 ), Brazilian ( 120 ), Lebanese ( 125 ) and American girls ( 126 ) ( Table 1 ).…”
Section: Precocious Puberty During the Covid-19 Pandemic: Current Dat...supporting
confidence: 86%
“…Worldwide many research groups ( 103 , 112 117 , 120 , 121 , 125 , 126 ) have reported similar results. For example, Acar et al.…”
Section: Precocious Puberty During the Covid-19 Pandemic: Current Dat...mentioning
confidence: 66%
See 1 more Smart Citation
“…Recently, several centers of pediatric endocrinology worldwide, including ours, have observed a further significant increase in the number of girls presenting with precocious or early puberty since mid-2020 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). During this period, corresponding to the first wave of COVID-19 pandemic, the Italian government imposed a strict lockdown across the country, in order to reduce the transmission rate and to avoid hospital bed saturation.…”
Section: Introductionmentioning
confidence: 89%
“…Chioma et al. build on the hypothesis that the COVID-19 pandemic triggers pathological processes in humans ( 4 , 5 ) to report a higher prevalence of rapidly progressive central precocious puberty (CPP) in girls during the COVID-19 pandemic from 2019 to 2022. Their finding that the prevalence declined after the peak of the pandemic suggests that the SARS-CoV-2 virus, or pandemic-associated environmental and psychosomatic changes could play a role in triggering CPP in girls.…”
mentioning
confidence: 99%